2018
DOI: 10.1016/j.molmet.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in the pathogenesis of type 2 diabetes in humans

Abstract: BackgroundType 2 diabetes (T2D) is a multifactorial, polygenic disease caused by impaired insulin secretion and insulin resistance. Genome-wide association studies (GWAS) were expected to resolve a large part of the genetic component of diabetes; yet, the single nucleotide polymorphisms identified by GWAS explain less than 20% of the estimated heritability for T2D. There was subsequently a need to look elsewhere to find disease-causing factors. Mechanisms mediating the interaction between environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 141 publications
(184 reference statements)
1
111
0
5
Order By: Relevance
“…Based on these findings, it is speculated that an interaction between PA and susceptibility genes may also have a decreased effect on T2DM. Recently, DNA methylation is believed to be a potential epigenetic mechanism to explain the interactions between lifestyle changes and genetic variation [29,30]. Barrès et al [31] have observed that decreased DNA methylations in response to acute exercise intervention induced a dose-dependent expression of metabolic genes in human skeletal muscle.…”
Section: Doi: 101159/000500110mentioning
confidence: 99%
“…Based on these findings, it is speculated that an interaction between PA and susceptibility genes may also have a decreased effect on T2DM. Recently, DNA methylation is believed to be a potential epigenetic mechanism to explain the interactions between lifestyle changes and genetic variation [29,30]. Barrès et al [31] have observed that decreased DNA methylations in response to acute exercise intervention induced a dose-dependent expression of metabolic genes in human skeletal muscle.…”
Section: Doi: 101159/000500110mentioning
confidence: 99%
“…It results from an intricate interaction between genetic make-up and environment, suggesting it's orchestrated by epigenetic mechanisms. In fact, a plethora of studies have found that changes in DNA methylation are associated with metabolic dysregulation [1, 2], but methylation's functional role is poorly understood.…”
mentioning
confidence: 99%
“…DNA methylation is thus thought to play a key role in responding to the environment and generating trait variation, including variation in disease susceptibility. In support of this idea, methylation levels have been associated with diabetes [3,4], autoimmune diseases [5][6][7], metabolic disorders [8][9][10], neurological disorders [11,12], and various forms of cancer [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%